2022
DOI: 10.5194/acp-2021-1045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement Report: Optical properties and sources of water-soluble brown carbon in Tianjin, North China: insights from organic molecular compositions

Abstract: Abstract. Brown carbon (BrC) aerosols exert vital impacts on climate change and atmospheric photochemistry due to their light absorption in the wavelength range from near-ultraviolet (UV) to visible light. However, the optical properties and formation mechanisms of ambient BrC remain poorly understood, limiting the estimation of their radiative forcing. In the present study, fine aerosols (PM2.5) were collected during 2016–2017 on a day/night basis over urban Tianjin, a megacity in North China, to obtain seaso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 72 publications
(115 reference statements)
2
12
0
Order By: Relevance
“…Therefore, we consider that LO-HULIS may be oxidized into HO-HULIS. This is consistent with other studies (Deng et al, 2022;.…”
Section: Sources Of Chromophores and Organic Aerosolsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, we consider that LO-HULIS may be oxidized into HO-HULIS. This is consistent with other studies (Deng et al, 2022;.…”
Section: Sources Of Chromophores and Organic Aerosolsupporting
confidence: 94%
“…In contrast, HO-HULIS and phenol-and naphthalene-like chromophores showed an anti-correlation with this diurnal evolution. Deng et al (2022) also found that LO-HULIS components contributed more at nighttime and HO-HULIS obviously increased in daytime during the winter in Tianjin, northern China. The characteristics of LO-HULIS are a low oxidizing state and high double bond equivalent.…”
Section: Sources Of Chromophores and Organic Aerosolmentioning
confidence: 73%
“…Yuan et al, 2021), Yulin (Lei et al, 2018), and Tianjin (J. Deng et al, 2022) at the same wavelength. The time-series of hourly light absorption of WS-BrC is shown in Figure 3b.…”
Section: Light-absorption Of Water-soluble Organic Carbonmentioning
confidence: 95%
“…For example, J. Deng et al (2022) revealed that wintertime BrC in Tianjin was predominately affected by equivalent contribution of fossil fuels combustion (30%) and biomass burning (30.7%), while the contribution of bioaerosol emission and biogenic Secondary Organic Aerosol (SOA) formation accounted for more than 60% of BrC in summer. Sources of BrC in northwest China also exhibited similar seasonal variations as those in Tianjin (Yuan et al, 2020).…”
mentioning
confidence: 99%
“…Therefore, the HULIS fractions exhibit relatively high absorption at UV and short visible wavelengths and relatively low absorption at long visible wavelengths, which results in relatively high AAE values. Moreover, the AAE values of HULIS did not present significant variation during the entire haze process, which could be related to the evolution of HULIS chromophores in different stages (Jiang et al, 2020;Huang et al, 2018;Deng et al, 2022). At first, the enhanced oxidation of aromatic species on haze days could lead to the bleaching or degradation of chromophores (a detailed explanation is provided in Sect.…”
Section: Light Absorptionmentioning
confidence: 99%